Studies and Application of Sialylated Milk Components on Regulating Neonatal Gut Microbiota and Health - Wang, Yushuang; Ze, Xiaolei; Rui, Binqi; Li, Xinke; Zeng, Nina; Yuan, Jieli; Li, Wenzhe; Yan, Jingyu; Li, Ming (Frontiers in Nutrition, 2021)
Breast milk is rich in sialic acids (SA), which are commonly combined with milk oligosaccharides and glycoconjugates. As a functional nutrient component, SA-containing milk components have received increasing attention in recent years. Sialylated human milk oligosaccharides (HMOs) have been demonstrated to promote the growth and metabolism of beneficial gut microbiota in infants, bringing positive outcomes to intestinal health and immune function. They also exhibit antiviral and bacteriostatic activities in the intestinal mucosa of new-borns, thereby inhibiting the adhesion of pathogens to host cells. These properties play a pivotal role in regulating the intestinal microbial ecosystem and preventing the occurrence of neonatal inflammatory diseases. In addition, some recent studies also support the promoting effects of sialylated HMOs on neonatal bone and brain development. In addition to HMOs, sialylated glycoproteins and glycolipids are abundant in milk, and are also critical to neonatal health. This article reviews the current research progress in the regulation of sialylated milk oligosaccharides and glycoconjugates on neonatal gut microbiota and health.